Hubungan Pengetahuan dengan Perilaku Personal-Hygiene saat Menstruasi pada Remaja Putri di Pondok Pesantren Miftahunnajah Sleman Yogyakarta - Rarania Tilana Wulandari; Intan Mutiara Putri; Esitra Herfanda (Poltekkes Kemenkes Padang, 2024)
Adolescents have problems related to genital hygiene, namely poor behavior or habits associated with maintaining the cleanliness of reproductive organs. Personal hygiene knowledge is vital during adolescent menstruation because it influences behavior in caring for reproductive health during menstruation. The purpose of this study is to evaluate the association between knowledge and personal hygiene behavior in adolescent girls during menstruation. This is quantitative study using a cross-sectional approach. The total sampling strategy was used to select 44 young women for this study. A questionnaire is being used to collect data in this study. The Fisher exact test was employed to analyze the data in this study. According to the findings of the study, 23 teenagers (52.3%) had adequate understanding of personal hygiene during menstruation. Personal hygiene habits among teenage females during menstruation was good for 41 of them (93.2%). The P-value for the analysis was 0.001 (0.05), demonstrating a link between knowledge and personal hygiene behavior. Conclusion : Good knowledge has been proven to cause good personal hygiene behavior in adolescents. Suggestion : Miftahunnajah Yogyakarta Islamic Boarding School can routinely provide information related to personal hygiene so that young women have good knowledge and personal hygiene behavior.